2020
DOI: 10.1038/s41598-020-73384-7
|View full text |Cite
|
Sign up to set email alerts
|

Pre-diagnostic biomarkers of type 2 diabetes identified in the UAE’s obese national population using targeted metabolomics

Abstract: Currently, type 2 diabetes mellitus (T2DM) and obesity are major global public health issues, and their prevalence in the United Arab Emirates (UAE) are among the highest in the world. In 2019, The UAE diabetes national prevalence was 15.4%. In recent years there has been a considerable investigation of predictive biomarkers associated with these conditions. This study analysed fasting (8 h) blood samples from an obese, normoglycemic cohort and an obese, T2DM cohort of UAE nationals, employing clinical chemist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…Amino acids (AAs) are crucial biological compounds that play a key metabolic and physiological role in all living organisms [66]. It was confirmed that these metabolites are useful diagnostic markers because they are considerably altered in prediabetes state and continue to increase during T2DM progression [67]. The Framingham Offspring Study has shown that elevated AAs were able to predict an increased risk of T2DM up to 12 years prior to disease onset [68].…”
Section: Discussionmentioning
confidence: 99%
“…Amino acids (AAs) are crucial biological compounds that play a key metabolic and physiological role in all living organisms [66]. It was confirmed that these metabolites are useful diagnostic markers because they are considerably altered in prediabetes state and continue to increase during T2DM progression [67]. The Framingham Offspring Study has shown that elevated AAs were able to predict an increased risk of T2DM up to 12 years prior to disease onset [68].…”
Section: Discussionmentioning
confidence: 99%
“…The potential positive association between SM C18:0 and endometrial cancer risk is in line with a recent report of a positive association of SM C18:0 with the endometrioid subtype of ovarian cancer in a prospective cohort [ 36 ]. Associations between sphingomyelins and diabetes and insulin resistance have also been observed and may partly explain their association with endometrial cancer [ 37 , 38 ]. Alterations of sphingolipid metabolism have been previously shown in endometrial cancer tissue compared to healthy endometrium [ 39 ] as well as in plasma of endometrial cancer patients compared to controls [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the two ACs found in our study were increased in the saliva of obese dogs compared to normal dogs. The ACs were positively correlated with the fat-free mass index in a previous study in humans [ 21 ]; furthermore, they were increased in obesity development and T2DM during pregnancy in women [ 30 ] and situations of obesity-related insulin resistance [ 24 ].…”
Section: Discussionmentioning
confidence: 92%
“…Salivary sphingolipids were significantly increased in the obese group compared to the control. Sphingomyelin plays a role in cell apoptosis by its hydrolysis into ceramide, which is in turn responsible for the induction of apoptosis and involvement in inflammatory processes [ 24 ]. Ceramides are involved in insulin-mediated glucose uptake and are thought to play an essential role in the development of insulin resistance [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation